ANALYSIS OF THE FACTORS INFLUENCING SATISFACTION IN BUILDING USER TRUST IN THE SKULID APPLICATION: AN INTEGRATED TAM AND UTAUT APPROACH - Eva Megawaty, Lellyana; Riza, Fahrul; Krispimandoyo, Denpharanto Agung (International Journal of Cultural and Social Science, 2026)
This study examines the determinants of user satisfaction and trust in Skul.id, an e-learning application developed by Telkomsel. Integrating the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), the study analyzes the effects of Perceived Usefulness, Perceived Ease of Use, Performance Expectancy, Effort Expectancy, and Facilitating Conditions on User Satisfaction and Trust. A quantitative approach was employed using an online questionnaire distributed to students who had used Skul.id for at least three months. Data from respondents selected through non-propability convenience sampling were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that all examined factors significantly and positively affect user satisfaction, with effort expectancy exerting the strongest influence. Gender and experience do not significantly moderate these relationships, suggesting relatively homogeneous technology adoption behavior among digital native students. Furthermore, satisfaction explains 67% of the variance in user trust, demonstrating its central role in trust formation. These findings confirm the applicability of TAM and UTAUT in youth-oriented e-learning contexts and highlight the importance of enhancing learning benefits, usability, and technological support to strengthen user trust and loyalty.